RESTRICTIONS IN THE SEMANTIC INTERPRETATION OF ENGLISH AND SPANISH COMPOUNDS - Marqueta, Bárbara (IBERIA: An International Journal of Theoretical Linguistics, 2018)
In this paper we claim that the differences between the semantic interpretation of English and Spanish compounds having identical categories (i.e. Noun + Noun) are determined by their syntactic structure. Assuming the already well-known division between structural semantics (the meaning provided by the syntactic structure) and conceptual semantics (the idiosyncratic meaning with which the construction is stored in the lexicon), we will try to demonstrate that the most productive patterns of compounding in both languages display a systematic contrast: the English constructions (i.e. paperboard, red-haired or dish-washer) has less structural complexity than the Spanish ones (i.e. papel carton, pelirrojo or lavaplatos). As a consequence of that, the amount of conceptual meanings that each member of the three compound patterns can receive in the English language is considerably bigger than in the Spanish language. This correlation between structures and conceptual meaning will be tested with Noun+Noun compounds, Adjective+Noun compounds and, finally, with Noun+Verb compounds. The differences found in all of them are triggered by the kind of relational structure that links the lexical units inside the compounds.